Preparation method and application of high specific capacity biomass hard carbon material

By co-grafting modification of triallyl isocyanurate and thienyl acrylic acid on the biomass, combined with hydrothermal pre-charging and inorganic salts, the problem of high manufacturing cost and low specific capacity at high magnification of sodium ion battery hard carbon materials is solved, and high specific capacity and excellent electrochemical performance are achieved.

CN119774583APending Publication Date: 2025-04-08FUJIAN XINSEN CARBON

Patent Information

Application Number
CN202411981120.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing hard carbon anode material for sodium ion batteries is expensive to manufacture, especially at high magnification, which is difficult to meet industrial needs.

Method used

The biomass is co-grafted and modified by triallyl isocyanurate and thienyl acrylic acid, and the hard carbon material co-doped by hydrothermal pre-charging and inorganic salts are formed.

Benefits of technology

The electrochemical performance of hard carbon materials is improved, especially the specific capacity at high magnifications is significantly improved, and the 5C reversible specific capacity is above 330mAh·g-1, while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774583A_ABST
    Figure CN119774583A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a high-specific-capacity biomass hard carbon material, comprising the following steps: (S1) pretreatment: the biomass raw material is crushed and washed to obtain a pretreated material; (S2) graft modification: triallyl isocyanurate, thienyl acrylic acid, a photoinitiator, and an inhibitor are dissolved in alcohol to obtain a modified solution; the pretreated material is added to the modified solution for immersion and then subjected to graft polymerization reaction under ultraviolet light to obtain a modified biomass; (S3) hydrothermal precarbonization: the modified biomass is added to a mixed aqueous solution of phosphoric acid and zinc chloride for heating reaction to obtain a hard carbon precursor; (S4) pyrolysis carbonization: the hard carbon precursor is mixed with an inorganic salt and carbonized under an inert atmosphere, and then purified and ground to obtain a high-specific-capacity biomass hard carbon material. The hard carbon material finally obtained by the present invention is used as a negative electrode material in a sodium ion battery, and has excellent comprehensive electrochemical properties, especially a significant improvement in specific capacity at high rates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of secondary battery hard carbon materials, and in particular relates to a preparation method and application of a high specific capacity biomass hard carbon material. Background Art

[0002] Sodium-ion batteries (SIBs) are the most promising next-generation commercial batteries after lithium-ion batteries (LIBs). However, the large radius and atomic mass of sodium ions result in poor sodium ion deintercalation kinetics, making it difficult to embed into negative electrode materials, resulting in poor electrochemical performance of sodium ion batteries in many aspects, such as first efficiency, cycle stability, and rate performance. Therefore, the electrochemical performance of current sodium ion battery negative electrode materials cannot meet actual industrial needs. Hard carbon materials are currently the most widely studied negative electrode materials for sodium ion batteries, and hard carbon materials derived from biomass are currently the negative electrode materials for sodium ion batteries that are expected to be industrially mass-produced due to their wide sources of raw materials and low prices. However, current biomass hard carbon materials form low surface defects and narrow interlayer spacing structures during high-temperature carbonization, resulting in low sodium storage capacity and low charge-discharge specific capacity, especially at high rates.

[0003] CN114388736A discloses a method for preparing a hard carbon negative electrode for lithium / sodium ion batteries from biomass carbon, wherein the modified biomass carbon is subjected to acid washing, ball milling, and carbonization to obtain a hard carbon negative electrode material. The modification is to immerse the biomass carbon in a DMF and m-aminophenylurea hydrochloride solution with a volume ratio of 1-5:3. Although the process of this patent is relatively simple, the immersion modification effect is limited.

[0004] CN11323440A discloses a hard carbon negative electrode material with high initial efficiency and excellent cycle life. The material conductivity is increased by adding carbon nanotubes to the raw materials for preparation, but carbon nanotubes are expensive. Even if a small amount is added, the production cost of the hard carbon material will increase, which deviates from the original intention of using biomass carbon sources, which are cheap and easy to obtain.

[0005] CN117038976A discloses a method for preparing a modified biomass hard carbon material, which uses tris[2-(3-mercaptopropionyl)ethyl]isocyanurate as a modifier, and performs impregnation modification on the carbonized bioparticles, followed by calcination to obtain modified carbonized particles; however, there is a problem of low reversible specific capacity at high rates.

[0006] Therefore, there is an urgent need to develop a low-cost hard carbon material suitable for sodium ion batteries with excellent electrochemical performance, especially high specific capacity at high rates. Summary of the invention

[0007] In order to solve the problem in the prior art that the manufacturing cost of hard carbon negative electrode materials for sodium ion batteries is high, especially the problem that the specific capacity at high rate needs to be improved, the present invention proposes a method for preparing a high specific capacity biomass hard carbon material. When the prepared hard carbon material is used as a negative electrode active material for a sodium ion battery, it has a high specific capacity at high rate and excellent comprehensive electrochemical performance.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for preparing a high specific capacity biomass hard carbon material comprises the following steps:

[0010] (S1) pretreatment: the biomass raw material is crushed, alkali washed, water washed, and dried in sequence to obtain a pretreated material;

[0011] (S2) Graft modification: dissolving triallyl isocyanurate, thienyl acrylic acid, a photoinitiator, and a polymerization inhibitor in alcohol to obtain a modified solution; adding the pretreated material to the modified solution for immersion to obtain a solid-liquid mixture; then introducing an inert gas into the solid-liquid mixture and sealing it, and performing a graft polymerization reaction under ultraviolet light to obtain a modified biomass;

[0012] (S3) hydrothermal pre-carbonization: adding the modified biomass to a mixed aqueous solution of phosphoric acid and zinc chloride, heating the mixture in a sealed environment for reaction, cooling the mixture to room temperature after the reaction is completed, filtering the mixture, and drying the mixture to obtain a hard carbon precursor;

[0013] (S4) Pyrolysis carbonization: The hard carbon precursor is mixed with an inorganic salt and carbonized under an inert atmosphere to obtain a carbonized material; the carbonized material is then purified and ground to obtain a high specific capacity biomass hard carbon material.

[0014] The present invention creatively modifies the biomass carbon material, and grafts trifunctional triallyl isocyanurate and thienyl acrylic acid onto the macromolecular chain of the biomass. Since triallyl isocyanurate contains three allyl bonds, it can form a richer cross-linked network after grafting; and thienyl acrylic acid contains abundant carboxyl groups, which can produce intermolecular forces with the hydroxyl groups on the biomass, and can further enrich the cross-linked network structure after grafting onto the macromolecular chain of the biomass; that is, the co-grafting of triallyl isocyanurate and thienyl acrylic acid makes the modified biomass have a rich cross-linked network structure, thereby reducing the defects of the hard carbon material after sintering, improving the microscopic morphology, and being beneficial to improving the electrochemical performance of the hard carbon material. In addition, triallyl isocyanurate contains a high content of nitrogen; thienyl acrylic acid contains sulfur; in the subsequent high-temperature pyrolysis carbonization process, sulfur and nitrogen react with carbon to form abundant CS bonds and CN bonds, realizing nitrogen-sulfur co-doping of hard carbon materials, increasing the interlayer spacing, facilitating the embedding / de-embedding of sodium ions, and improving the wettability of the surface of hard carbon materials, further improving the specific capacity of hard carbon materials as electrode materials. Furthermore, triallyl isocyanurate and thienyl acrylic acid are both heterocyclic compounds containing large π bonds. After being grafted onto the macromolecular chain of biomass, their large π bonds can interact with the large π bonds of the benzene ring of biomass, which is beneficial to the subsequent hydrothermal pre-carbonization reaction. That is, triallyl isocyanurate and thienyl acrylic acid realize the co-grafting and cross-linking modification of biomass while carrying out nitrogen-sulfur co-doping, which is also beneficial to the hydrothermal pre-carbonization reaction. The biomass after the above modification and hydrothermal pre-carbonization is finally calcined at high temperature with metal salts. During the pyrolysis carbonization process, the metal salts inhibit the agglomeration and stacking of the carbon source during the calcination process. In summary, the present invention obtains a nitrogen-sulfur co-doped hard carbon material with a large interlayer spacing through the above co-grafting cross-linking modification, hydrothermal pre-carbonization and coordinated calcination, which improves the electrochemical properties of the hard carbon material, especially the specific capacity at high rates.

[0015] Furthermore, in step (S1), the biomass raw material is at least one of peanut shells, coconut shells, apricot shells, hazelnut shells, and walnut shells. The present invention uses cheap and readily available bulk biological raw materials to ensure the needs of large-scale industrial production.

[0016] Furthermore, in step (S1), the crushing is to crush into 200-400 meshes to facilitate the subsequent grafting reaction; the crushing method is air flow crushing, high-speed crushing or ball milling; the alkali washing conditions are: immersing in a 50-60°C, 5-10wt% NaOH and / or KOH aqueous solution for 2-4h under stirring conditions of 60-100rpm; the water washing is to wash with water until the pH of the effluent is 8-9; the drying is to dry at 80-120°C to a water content of ≤5wt%.

[0017] Furthermore, in step (S2), the thienyl acrylic acid is selected from at least one of 3-(2-thienyl) acrylic acid, 3-(3-thienyl) acrylic acid, 2-phenyl-3-(2-thienyl) acrylic acid, and 3-(3-methyl-2-thiophene) acrylic acid.

[0018] Furthermore, in step (S2), the photoinitiator is selected from at least one of benzophenone, 2,2-dimethoxyacetophenone, and 2,2-diethoxyacetophenone; the inhibitor is ferrous sulfate; and the alcohol is selected from at least one of ethanol, propanol, and isopropanol.

[0019] Furthermore, in step (S2), the molar ratio of triallyl isocyanurate to thienyl acrylic acid is 1:(0.3-0.6), preferably 1:(0.4-0.5). Triallyl isocyanurate and thienyl acrylic acid achieve co-grafting and cross-linking modification of biomass while performing nitrogen and sulfur co-doping, which is also beneficial to the hydrothermal pre-carbonization reaction.

[0020] Furthermore, in step (S2), the amount of the photoinitiator is 3-5% of the total molar amount of triallyl isocyanurate and thienyl acrylic acid. The amount of the photoinitiator needs to be controlled within the above range. When the amount of the photoinitiator is too low, the reaction is incomplete and the grafting rate is low. As the concentration of the photoinitiator increases, the number of free radical active points generated on the surface of the biomass increases, and the grafting rate rises. However, when the concentration of the photoinitiator is too high, a shielding effect will be caused, reducing the intensity of ultraviolet light at the interface between the solution and the biomass matrix. At the same time, when the amount of the photoinitiator increases, it is easy to induce the self-polymerization of triallyl isocyanurate and the self-polymerization of thienyl acrylic acid, which in turn reduces the grafting rate of the biomass.

[0021] Furthermore, in step (S2), the amount of the polymerization inhibitor is 0.03-0.06wt% of the total mass of triallyl isocyanurate and thienyl acrylic acid, and the role of the polymerization inhibitor is to prevent the self-polymerization of triallyl isocyanurate and thienyl acrylic acid; the ratio of the amount of the alcohol to the total mass of triallyl isocyanurate and thienyl acrylic acid is 1L: (10-30)g.

[0022] Furthermore, in step (S2), the pre-treated material is 5 to 9 times the total mass of triallyl isocyanurate and thienyl acrylic acid.

[0023] Furthermore, in step (S2), the immersion conditions are: temperature 45-65° C., time 2-5 hours.

[0024] Furthermore, in step (S2), the inert gas is nitrogen and / or argon; the wavelength of the ultraviolet light is 300 to 380 nm; and the irradiation time is 20 to 30 min.

[0025] Furthermore, in step (S3), the mass ratio of phosphoric acid to zinc chloride is 1:(0.2-0.4); the total concentration of the mixed aqueous solution is 30-40wt%; the solid-liquid ratio of the modified biomass to the mixed aqueous solution is 1kg:(2-5)L. Phosphoric acid is a Lewis acid, which can accelerate the decomposition of cellulose and lignin in biomass and promote the condensation reaction of aromatic hydrocarbons during hydrothermal precarbonization; zinc chloride has a strong catalytic dehydroxylation and dehydration effect, so that hydrogen and oxygen in the raw material escape in the form of water vapor, thereby inhibiting the production of tar and avoiding pore blockage; the combined effect of the two is conducive to hydrothermal precarbonization and improving porosity.

[0026] Furthermore, in step (S3), the conditions of the heating reaction are: keeping warm at 70-100° C. for 2-5 hours; and the drying is drying to constant weight.

[0027] Furthermore, in step (S4), the inorganic salt is K2SO4, Na2SO 4、 At least one of KCl and NaCl, the mass ratio of the inorganic salt to the hard carbon precursor is 1: (15-20). The inorganic metal salt can play an isolating role and inhibit the agglomeration and stacking of the carbon source during the calcination process.

[0028] Furthermore, in step (S4), the carbonization conditions are: temperature 600-900°C, time 6-8h; the inert atmosphere has an oxygen content of less than 1%, preferably less than 0.1%, such as nitrogen and / or argon atmosphere.

[0029] Furthermore, in step (S4), the purification is sequentially flotation, hydrochloric acid rinsing, water washing, and drying; the grinding is grinding until D50 is 5 to 10 μm, and the grinding equipment is not particularly limited and can be conventional in the art, such as air flow grinding equipment and ball milling.

[0030] Furthermore, the flotation is flow-through frothing flotation, and the purpose of flotation is to preliminarily remove iron impurities and ash classification components such as mud, sand, etc.; the conditions of the hydrochloric acid rinsing are: the carbonized material after flotation and the dilute hydrochloric acid solution with a concentration of 3-8wt% are mixed and stirred evenly in a reactor, and refluxed for 2-4h, the amount of dilute hydrochloric acid used is 4-6 times the mass of the carbonized material after flotation, and the purpose of the hydrochloric acid rinsing is to remove metal ash impurities; the water washing is to wash with water until the pH of the effluent is 6.8-7.2; the drying is to dry to constant weight.

[0031] The present invention also provides a sodium ion battery, the negative electrode of which comprises the high specific capacity biomass hard carbon material prepared by the above preparation method.

[0032] The beneficial effects of the present invention are as follows:

[0033] 1) The present invention uses triallyl isocyanurate and thienyl acrylic acid to co-graft modify biomass. The modified biomass has a rich cross-linked network structure, which reduces the defects of the hard carbon material after sintering, improves the micromorphology, and is beneficial to improving the electrochemical properties of the hard carbon material. The introduction of triallyl isocyanurate and thienyl acrylic acid simultaneously realizes the nitrogen-sulfur co-doping of the hard carbon material, and is also beneficial to hydrothermal pre-carbonization. The present invention obtains a nitrogen-sulfur co-doped hard carbon material with a large interlayer spacing through co-grafting cross-linking modification, hydrothermal pre-carbonization, and coordinated calcination with inorganic salts; the sodium ion battery made of the negative electrode material has excellent comprehensive electrochemical properties, especially the specific capacity at high rate is significantly improved, and the 5C reversible specific capacity is 330mAh·g -1 above.

[0034] 2) The present invention uses cheap and readily available biomass as a carbon source, and the ultraviolet light grafting modification takes a short time and has high efficiency. Therefore, the preparation method of the present invention is simple and easy to operate, has low energy consumption, and low overall cost, and is suitable for large-scale process production. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the SEM picture of Example 1. DETAILED DESCRIPTION

[0036] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below. The following examples are convenient for better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified.

[0037] Example 1

[0038] (S1) Pretreatment: The peanut shells were ball-milled to 325 mesh, and then placed in a 50° C., 10 wt % NaOH aqueous solution and immersed for 3 h under stirring at 80 rpm; then washed with water until the pH of the effluent was 8, and then dried at 90° C. for 24 h until the water content was 3 wt %, to obtain a pretreated material;

[0039] (S2) Graft modification: 249 g (1 mol) of triallyl isocyanurate, 46.2 g (0.3 mol) of 3-(2-thienyl) acrylic acid, 10.9 g (0.06 mol) of benzophenone, and 0.15 g of ferrous sulfate as an inhibitor were added to 10 L of isopropanol, and completely dissolved in a stirred reactor to obtain a modified solution; then 2000 g of the pretreated material was added to the modified solution, and immersed at 50° C. for 3 hours to obtain a solid-liquid mixture; after the immersion, nitrogen was introduced into the solid-liquid mixture, the hollow was eliminated and the mixture was sealed, and then the ultraviolet lamp was turned on, and the mixture was irradiated under 350 nm ultraviolet light for 20 minutes under stirring to carry out a graft polymerization reaction; after the ultraviolet light irradiation was completed, the reacted material was placed in a Soxhlet extractor containing acetone for extraction, washing, and drying to obtain a modified biomass;

[0040] (S3) Hydrothermal pre-carbonization: Phosphoric acid and zinc chloride are dissolved in pure water at a mass ratio of 1:0.2 to prepare a mixed aqueous solution with a total concentration of 30 wt%; then the modified biomass is placed in the mixed aqueous solution at a solid-liquid ratio of 1 kg:3 L, and kept warm at 80° C. for 4 h under closed stirring; after the insulation is completed, the mixture is cooled to room temperature, filtered, and dried at 85° C. to constant weight to obtain a hard carbon precursor;

[0041] (S4) Pyrolysis carbonization: The hard carbon precursor and Na2SO4 are added into a rotary atmosphere furnace at a mass ratio of 15:1, and carbonized at 800°C for 6 hours at a rotation speed of 3 rpm in a nitrogen atmosphere to obtain a carbonized material; the carbonized material is sequentially subjected to flow bubble flotation, rinsed with 5 wt% dilute hydrochloric acid, washed with water until the pH of the effluent is 7, dried at 85°C to constant weight, and finally ball milled to a D50 of 6.1 μm to obtain a high specific capacity biomass hard carbon material.

[0042] Figure 1 This is the SEM image of the biomass hard carbon material obtained in Example 1.

[0043] Example 2

[0044] The rest is the same as Example 1, except that the amounts of 3-(2-thienyl)acrylic acid and benzophenone in step (S2) are different, wherein the amount of 3-(2-thienyl)acrylic acid is 61.6 g (0.4 mol). Finally, a high specific capacity biomass hard carbon material with a D50 of 6.4 μm is obtained.

[0045] Example 3

[0046] The rest is the same as Example 1, except that the amounts of 3-(2-thienyl)acrylic acid and benzophenone in step (S2) are different, wherein the amount of 3-(2-thienyl)acrylic acid is 77 g (0.5 mol). Finally, a high specific capacity biomass hard carbon material with a D50 of 5.8 μm is obtained.

[0047] Example 4

[0048] The rest is the same as Example 1, except that the amounts of 3-(2-thienyl)acrylic acid and benzophenone in step (S2) are different, wherein the amount of 3-(2-thienyl)acrylic acid is 92.4 g (0.6 mol). Finally, a high specific capacity biomass hard carbon material with a D50 of 6.3 μm is obtained.

[0049] Example 5

[0050] The rest is the same as Example 1, except that 50.4 g (0.3 mol) of 3-(3-methyl-2-thiophene) acrylic acid is used in step (S2) to replace 3-(2-thienyl) acrylic acid. Finally, a high specific capacity biomass hard carbon material with a D50 of 6.2 μm is obtained.

[0051] Example 6

[0052] The rest is the same as Example 1, except that coconut shells are used instead of peanut shells in step (S1); the mass ratio of phosphoric acid to zinc chloride in step (S3) is 1:0.4; NaCl is used instead of Na2SO4 in step (S4). Finally, a high specific capacity biomass hard carbon material with a D50 of 6.5 μm is obtained.

[0053] Comparative Example 1

[0054] The rest is the same as Example 1, except that: step (S2) is omitted; and in step (S3), pretreated material is used instead of modified biomass.

[0055] Comparative Example 2

[0056] The rest is the same as Example 1, except that: in step (S2), 3-(2-thienyl)acrylic acid is not added, and the amount of triallyl isocyanurate added is changed to 1.3 mol.

[0057] Comparative Example 3

[0058] The rest is the same as Example 1, except that: triallyl isocyanurate is not added in step (S2), and the amount of 3-(2-thienyl)acrylic acid added is changed to 1.3 mol.

[0059] Testing and analysis

[0060] 1) The nitrogen and sulfur content of the biomass hard carbon materials prepared in the examples and comparative examples were analyzed using the vario ELcube element analyzer produced by Elementar of Germany. The data are shown in Table 1.

[0061] 2) The electrochemical performance of the biomass hard carbon material prepared in the embodiment and the comparative example is tested. The specific steps are as follows: the hard carbon material prepared in the embodiment or the comparative example is used as the active ingredient, mixed with a binder of 1% CMC and a conductive agent Super P in a mass ratio of 8:1:1, and a solvent NMP is added to prepare a negative electrode slurry. An automatic film coating and drying machine is used to evenly coat the negative electrode slurry on an aluminum foil current collector with a scraper, with a coating thickness of 150±1μm, and a circular electrode sheet with a diameter of 14mm is prepared after vacuum drying. A sodium sheet is used as the counter electrode, and glass fiber is used as the diaphragm. The electrolyte is a NaClO4 solution with a NaClO4 concentration of 1mol / L. The solvent is a mixture of ethylene carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1. The half-cell is assembled in a glove box. After assembly, the battery is charged at 25mAh·g -1 The test was carried out at a current density of (0.1C) and a test range of 0.001-2.0 V. The electrochemical performance test results are shown in Table 1 below.

[0062] Table 1 Element content test and electrochemical performance test of hard carbon materials

[0063]

[0064]

[0065] As can be seen from Table 1, the sodium ion battery prepared by the hard carbon material prepared by the preparation method of the present invention as the negative electrode active material has excellent comprehensive electrochemical performance, especially the specific capacity at high rate is significantly improved, and the 5C reversible specific capacity is 330 mAh·g -1 In Comparative Example 1, no grafting modification was performed, and the comprehensive electrochemical performance of the sodium ion battery made of the hard carbon material as the negative electrode active material was poor. Although the 0.1C reversible specific capacity and the first coulombic efficiency of the sodium ion battery made of the hard carbon material as the negative electrode active material in Comparative Examples 2 and 3 were high, the reversible specific capacity at high rate was low.

Claims

1. A method for preparing a high specific capacity biomass hard carbon material, characterized in that: The following steps are involved: (S1) pretreatment: the biomass raw material is crushed, alkali washed, water washed, and dried in sequence to obtain a pretreated material; (S2) Graft modification: dissolving triallyl isocyanurate, thienyl acrylic acid, a photoinitiator, and a polymerization inhibitor in alcohol to obtain a modified solution; The pretreated material is added into the modified liquid for immersion to obtain a solid-liquid mixture; an inert gas is then introduced into the solid-liquid mixture and sealed, and a graft polymerization reaction is performed under ultraviolet light to obtain a modified biomass; (S3) hydrothermal pre-carbonization: adding the modified biomass to a mixed aqueous solution of phosphoric acid and zinc chloride, heating the mixture in a sealed environment for reaction, cooling the mixture to room temperature after the reaction is completed, filtering the mixture, and drying the mixture to obtain a hard carbon precursor; (S4) pyrolysis carbonization: mixing the hard carbon precursor with an inorganic salt and carbonizing the mixture under an inert atmosphere to obtain a carbonized material; After purification and grinding, high specific capacity biomass hard carbon material is obtained.

2. The preparation method according to claim 1, characterized in that: In step (S1), the biomass raw material is at least one of peanut shells, coconut shells, apricot shells, hazelnut shells, and walnut shells; and / or The crushing is to crush into 200-400 meshes; the alkali washing condition is: immersing in 50-60°C, 5-10wt% NaOH and / or KOH aqueous solution for 2-4h under 60-100rpm stirring condition; the water washing is to wash with water until the pH value of the effluent is 8-9; the drying is to dry at 80-120°C until the water content is ≤5wt%.

3. The preparation method according to claim 1, characterized in that: In step (S2), the thienyl acrylic acid is selected from at least one of 3-(2-thienyl) acrylic acid, 3-(3-thienyl) acrylic acid, 2-phenyl-3-(2-thienyl) acrylic acid, and 3-(3-methyl-2-thiophene) acrylic acid.

4. The preparation method according to claim 1, characterized in that: In step (S2), the photoinitiator is selected from at least one of benzophenone, 2,2-dimethoxyacetophenone, and 2,2-diethoxyacetophenone; the inhibitor is ferrous sulfate; and the alcohol is selected from at least one of ethanol, propanol, and isopropanol.

5. The preparation method according to claim 1, characterized in that: In step (S2), the molar ratio of triallyl isocyanurate to thienyl acrylic acid is 1:(0.3-0.6), preferably 1:(0.4-0.5).

6. The preparation method according to claim 1, characterized in that: In step (S2), the amount of the photoinitiator is 3-5% of the total molar amount of triallyl isocyanurate and thienyl acrylic acid; the amount of the inhibitor is 0.03-0.06wt% of the total mass of triallyl isocyanurate and thienyl acrylic acid; the ratio of the amount of the alcohol to the total mass of triallyl isocyanurate and thienyl acrylic acid is 1L: (10-30)g; the pretreated material is 5-9 times the total mass of triallyl isocyanurate and thienyl acrylic acid.

7. The preparation method according to claim 1, characterized in that: In step (S2), the immersion conditions are: temperature 45-65°C, time 2-5 hours; and / or The inert gas is nitrogen and / or argon; the wavelength of the ultraviolet light is 300-380 nm; and the irradiation time is 20-30 min.

8. The preparation method according to claim 1, characterized in that: In step (S3), the mass ratio of phosphoric acid to zinc chloride is 1:(0.2-0.4); the total concentration of the mixed aqueous solution is 30-40wt%; the solid-liquid ratio of the modified biomass to the mixed aqueous solution is 1kg:(2-5)L; and / or The heating reaction conditions are: keeping warm at 70-100° C. for 2-5 hours.

9. The preparation method according to claim 1, characterized in that: In step (S4), the inorganic salt is K2SO4, Na2SO 4、 At least one of KCl and NaCl, the mass ratio of the inorganic salt to the hard carbon precursor is 1: (15-20); and / or The carbonization conditions are: temperature 600-900°C, time 6-8h; the inert atmosphere has an oxygen content of less than 1%, preferably less than 0.1%; the purification is sequentially flotation, hydrochloric acid rinsing, water washing, and drying; the grinding is grinding until D50 is 5-10μm.

10. A sodium ion battery, characterized in that: The negative electrode comprises a high specific capacity biomass hard carbon material prepared by the preparation method of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of modified biomass hard carbon material

    CN117038976A

Cited By

  • Preparation method of biomass hard carbon material, biomass hard carbon material and application of biomass hard carbon material

    CN121449042A